2012
DOI: 10.2503/jjshs1.81.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Surface Blushing and Qualitative Components of Japanese Apricot (Prunus mume Sieb. et Zucc.) ‘Nanko’ Fruit

Abstract: The relationships between surface blushing and the content of qualitative components of the Japanese apricot 'Nanko' fruit were investigated. Brightly blushed fruit covering over 25% of its surface had higher levels of citric acid, phenolics, and antioxidant activity in its flesh than non-blushed fruit. Shading apricot fruit from ultraviolet (UV) light for about 3 weeks before harvest produced a clear decrease in surface blushing, phenolic content, and antioxidant activity. UV-B irradiation for 12 h to the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Apricot was chosen as a model fruit because it is commonly prepared in dried form. Also, a recent study of a related fruit species, Prunus mume , showed that surface blushing, phenolic content, and antioxidant activity of the fruit increased when fruit were exposed to preharvest sunlight (Oe and others ). So, it was hypothesized that similar quality improvements might occur in apricots exposed to certain bands of the solar spectrum.…”
Section: Introductionmentioning
confidence: 98%
“…Apricot was chosen as a model fruit because it is commonly prepared in dried form. Also, a recent study of a related fruit species, Prunus mume , showed that surface blushing, phenolic content, and antioxidant activity of the fruit increased when fruit were exposed to preharvest sunlight (Oe and others ). So, it was hypothesized that similar quality improvements might occur in apricots exposed to certain bands of the solar spectrum.…”
Section: Introductionmentioning
confidence: 98%